Assessment of Soico-Demographic Factors and Dietary Habits among Hypertension Patient in Derna, Libya - Fareha Hamd Younis,; Sajida Mostafa Tarfaya,; Rahma Shukri Benarous, (AlQalam Journal of Medical and Applied Sciences, 2024)
Hypertension is a global public health problem. It is one of the major causes of premature death worldwide. This study carried out in Derna city Libya to study socio-demographic characteristics and to assess dietary habits among 150 hypertension patients aged 20 to 96 years. Data were obtained from patients by cross-sectional then analyzed using SPSS version 24. The results revealed 100(66.7%) have family history. Additionally large number of patients were with history of diabetes mellitus 117(78.0%). Regarding the anthropometric measurements of patients 44.0 % category as overweight and 34.0 % were obese. In contrast, positive correlation was noted between body weight and different age groups of patients. Moreover, 66(44.0%) of them were consumed fruits every day also just about 12(8.0%) consumed vegetables each day. In addition, 50(33.3%) and 81(54.0%) of patients were consumed canned and fried food respectively every day. Moreover, 67(44.7%) and 52(34.7%) were consumed meat products and eggs respectively every day. Our investigations revealed that intakes of meat products, eggs, canned and fried food were high while consumption vegetables and fruits were relatively limited which linked to poor health and increased risk of hypertension complication. ارتفاع ضغط الدم هو مشكلة صحية عامة عالمية. وهو أحد الأسباب الرئيسية للوفاة المبكرة في جميع أنحاء العالم [1]. أجريت هذه الدراسة في مدينة درنة بليبيا لدراسة الخصائص الاجتماعية والديموغرافية وتقييم العادات الغذائية بين 150 مريضًا بارتفاع ضغط الدم تتراوح أعمارهم بين 20 إلى 96 عامًا. تم الحصول على البيانات من دراسة مقطعية للمرضى ثم تحليلها باستخدام برنامج SPSS الإصدار 24. وكشفت النتائج أن 100 (66.7٪) لديهم تاريخ عائلي. بالإضافة إلى ذلك، كان هناك عدد كبير من المرضى الذين لديهم تاريخ مع مرض السكري 117 (78.0٪). فيما يتعلق بالقياسات البشرية للمرضى، 44.0% فئة يعانون من زيادة الوزن و34.0% يعانون من السمنة المفرطة. في المقابل، لوحظ وجود علاقة إيجابية بين وزن الجسم والفئات العمرية المختلفة للمرضى. علاوة على ذلك، كان 66 (44.0٪) منهم يستهلكون الفواكه يوميًا، كما يستهلك حوالي 12 (8.0٪) الخضار يوميًا. إضافة إلى ذلك فإن نسبة استهلاك الحليب كامل الدسم 26.0% يومياً. علاوة على ذلك، تم تناول 50 (33.3٪) و81 (54.0٪) من المرضى الأطعمة المعلبة والمقلية على التوالي كل يوم. بالإضافة إلى ذلك، تم استهلاك 67 (44.7٪) و 52 (34.7٪) منتجات اللحوم والبيض على التوالي يوميا. كشفت تحقيقاتنا أن تناول منتجات الألبان وخاصة الحليب كامل الدسم ومنتجات اللحوم والبيض والأطعمة المعلبة والمقلية كانت مرتفعة بينما كان استهلاك الخضار والفواكه محدودًا نسبيًا مما يرتبط بسوء الصحة وزيادة خطر الإصابة بمضاعفات ارتفاع ضغط الدم